2014
DOI: 10.1111/jcap.12082
|View full text |Cite
|
Sign up to set email alerts
|

Latina Adolescent Sleep and Mood: An Ecological Momentary Assessment Pilot Study

Abstract: Interventions should encourage sleep-mood relationship awareness, and further research should identify significant differences to inform tailored interventions with adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 74 publications
2
12
0
Order By: Relevance
“…reported null findings [60][61][62][63][64][65][66]. Among studies reporting null results, the majority focused on the absence rather than presence of good sleep (i.e., adequate or restorative sleep).…”
Section: Effects Of Pa On Sleepmentioning
confidence: 99%
“…reported null findings [60][61][62][63][64][65][66]. Among studies reporting null results, the majority focused on the absence rather than presence of good sleep (i.e., adequate or restorative sleep).…”
Section: Effects Of Pa On Sleepmentioning
confidence: 99%
“…With regard to Latino youth, Garcia et al (2014) conducted research on the association between mood and sleep problems with a sample of Latina adolescents, and they provide a list of treatment considerations with this population. These recommendations included educating youth on the association between mood and sleep, training staff on warning signs of poor coping, emotional arousal, and worrying so that interventions can be employed, and teaching youth cognitive restructuring techniques to improve mood and sleep expectancies.…”
Section: Discussionmentioning
confidence: 99%
“…The application prompted to user to fill out the self-monitoring once a day and the items are consisting of nine that are mood, sleep, activity, medicine, anxiety, stress, cognitive problems, irritability and note. Using smartphone text massage, Garcia et al (2014) studied perceived sleep and mood for Latina adolescent. They concluded that inadequate sleep has been associated with negative outcomes of mental health, physical health, academic behavior and other behavior problems [24].…”
Section: B Sleep Quality Prediction Using Mobile Devicesmentioning
confidence: 99%